2 A.M. at The Cat's Pajamas : A Novel - Bertino, Marie-Helene (London Picador, 2014)
"As three lost souls search for love, music, and hope on the snow-covered streets of Philadelphia ... they will discover life's endless possibilities over the course of one magical night"
Keywords: Nightclubs -- Women teachers -- Pennsylvania--Philadelphia